A avaliação do processo de elaboração dos materiais didáticos para a educação a distância em rede - Mesquita, Ofélia Alencar de (2009)
This work tries to evaluate the development of teaching material for Distance Education in Network, in order to suggest new possibilities for its development. Is a qualitative research, which uses content analysis as method and checklist as tool. The data show from two classes, physics and literature, constituted by the Production Center, of the Virtual Institute UFC. The checklist is divided into three categories refered to as: educacional website, usability and hypermedia nodes. Each category is segmented into based on criteria rated on a scale ranging from 1 (completely inadequate) to 5 (totally appropriate). Classes are evaluated in three distinct phases: a lesson developed by the teacher-author, reviewed by professional of the didactic transition and published in a virtual learning environment, allowing an understanding of its evolution during production. The results show that: there are guidelines set for joint action and multidisciplinary development of materials; the action of each subject at different stages can define the adequacy or inadequacy of the learning units; are few the correlations made between the materials and AVAs; and that there is a deficiency, by the professionals in their understanding about the capabilities of the usability and of hypermedia nodes. These results highlight the roles of the subject in the course of drawing materials, showing that there are still many unknowns regarding the components of the materials,and on necessary changes to ensure that the subject identify, understand and use.